Motivasi Petani Untuk Mencapai Tujuan dalam Aktivitas Wirausaha: Sebuah Pendalaman Konseptual Melalui Literature Review - Mukti, Gema Wibawa; Charina, Anne; Kusumo, Rani Andriani Budi (Universitas Galuh, 2024)
Understanding an individual's ability to recognize the opportunities that exist in the surrounding environment has become an important issue in the study of entrepreneurship globally. Research on motivation that emerges from within an entrepreneur is still relatively little done by entrepreneurship researchers. This research aims to provide a better understanding of why a person chooses to become an entrepreneur and how they can achieve success in their business. This research uses a qualitative method, with literature review techniques. Goals consist of four categories, including external rewards, independence/autonomy, internal rewards, and a sense of security that comes from and for the family. A farmer runs a business not necessarily to achieve a large level of profit, often farmers run a business to pass on the inheritance from the family, or to become an independent person, so that they do not depend on others. This research is expected to explain and predict the behavior of farmers as an entrepreneur, namely by understanding how and why a goal is important for an entrepreneur. Furthermore, this study explains the process of achieving goals, which can motivate and influence farmers' entrepreneurial behavior. Finally, this research is expected to contribute to answering questions in entrepreneurship research, namely; How does an entrepreneur strive to build, pursue, and achieve their goals?